Peningkatan keterampilan menyelesaikan soal cerita keliling dan luas bangun datar melalui model pembelajaran logan avenue problem solving (laps) – heuristik pada peserta didik kelas iii sekolah dasar - Puput Nikmaturrohmah; Suharno Suharno; Siti Kamsiyati (Didaktika Dwija Indria, 2019)
This research aims to improve problem solving skills of circumference and area of plane object’s stories matter for third grade students of Mojosongo II No. 177 Elementary School in 2018/2019 academic year by applying Logan Avenue Problem Solving (LAPS) – Heuristic. This research consisted of two cycles, each cycle includes two learnings. Subject and data source in this reaserch were teacher and student of third grade Mojosongo II No. 177 Elementary School. Interviews, observations, tests, and document analysis is this research datas collection. This research uses descriptive comparative analysis techniques and interactive analysis techniques. Source triangulation and technical triangulation used for data validity. Classical completeness of students in initial condition was 3.57%, in first cycle showed 46.43%. then in second cycle showed 82.14%.Keywords: circumference and area of plane object’s stories matter, Logan Avenue Problem Solving (LAPS) – Heuristic, problem solving skills, elementary school